Evaluasi Kesuksesan Portal Online Dengan Pendekatan Model DeLone dan McLean (Studi Kasus: Perusahaan XYZ) - Dien Novita (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
XYZ company has used the information system to survive and develop to adjust the times and business direction that exists at this time, one of which is the online portal, the total role of portal online is large and there is no measurement of whether the information, systems, and services are sufficient quality, so the author is interested in evaluating the success of the online portal by using the DeLone and McLean model approach. To measure the influence between existing variables, in this study the author uses six variables in the DeLone model, namely information quality, quality system, quality of service, user satisfaction, usage, and net benefits, where processing of statistical data is processed using SmartPLS statistical data processing software, while the results of this study are quality of information does not affect user satisfaction but the quality of information affects the use variable, service quality affects user satisfaction but does not have an influence on the use of a system, system quality has an influence on usage and also user satisfaction variables, user satisfaction variables have no effect on benefits net benefits, user satisfaction does not affect usage, use does not affect netbenefits, usage has an effect on user satisfaction, net benefits have no effect on user use and satisfaction.